The Application of Criminal Sanctions to Law Enforcement Officers Involved in Online Gambling, from the Perspective of Legal Positivism.: Penerapan Sanksi Pidana Pelaku Judi Online yang Dilakukan oleh Oknum Kepolisian dalam Perspektif Positivisme Hukum - Sari, Pika; Amrullah , M. Arief; Setyawan, Efendi; Yanuarto, Totok (Indonesian Journal of Innovation Studies, 2023)
This scientific article provides an in-depth analysis of the regulatory framework and legal consequences surrounding online gambling in Indonesia, with a specific focus on the provisions outlined in Law Number 19 of 2016 on Information and Electronic Transactions. The primary goal of this research is to examine the legal mechanisms in place to combat cybercrime, particularly online gambling, and their effectiveness in curbing illicit activities in the digital realm. To achieve this, the study employs a comprehensive legal analysis, scrutinizing Pasal 27(2) and Pasal 45(2) of the aforementioned law, which pertain to penalties for online fraud and the legal implications of such actions. The results of this analysis shed light on the legal consequences that individuals engaging in online gambling may face, emphasizing the seriousness with which Indonesian authorities regard such activities. Moreover, the implications of these findings underscore the need for stricter enforcement of cybercrime legislation, highlighting the importance of a robust legal framework in the digital age to ensure a secure and accountable online environment in Indonesia. This study contributes to the scholarly understanding of the legal aspects of online gambling and provides a foundation for further research and policy development in the field of digital law and cybercrime prevention. Highlights: Stringent Cybercrime Laws: Indonesian legislation (Law No. 19/2016) includes provisions to combat online gambling, emphasizing the severity of cybercrimes and penalties. Legal Consequences for Offenders: The study examines Pasal 27(2) and Pasal 45(2) to reveal the potential legal ramifications faced by those engaging in online gambling. Call for Strengthened Enforcement: The research underscores the necessity of robust enforcement to maintain a secure digital environment in Indonesia. Keywords: Online Gambling Regulations, Cybercrime Legislation, Legal Implications, Indonesia's Legal Framework, Digital Law Enforcement